Development of an immunochromatographic strip assay based on a monoclonal antibody for detection of cimaterol. Issue 1 (1st January 2019) - Liu, Ziying; Liu, Liqiang; Cui, Gang; Wu, Xiaoling; Kuang, Hua
ABSTRACT: An anti-cimaterol (cima) monoclonal antibody, 2H8, was prepared and used to develop an indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and an immunochromatographic test strip assay for the detection of cima, a newly described β-agonist. The half-maximal inhibitory concentration of the antibody was 1.56 ng/mL, and no cross-reactivity with other β-adrenergic agonists was observed. The antibody's limit of detection was 0.416 ng/mL, and its linear range of detection was 0.416–5.868 ng/mL. The recovery rates of cima in swine urine ranged from 86% to 92.5%, and the test strip had a cut-off value of 10 ng/mL. Both ic-ELISA and the developed strip assay are effective when detecting cima in swine urine.